EFEKTIFITAS TERAPI MINDFULNESS TERHADAP PENURUNAN KECEMASAN PADA IBU DENGAN RIMIGRAVIDA TRIMESTER 2 DI PUSKESMAS PURBALINGGA - sonia gandi, Febrianti; Apriliyani, Ita (STIKES dan AKZI Karya Husada Kediri, 2024)
Anxiety is a feeling of worry, nervousness, or even fear of something uncertain and present simultaneously that affects or causes depression. Anxiety during pregnancy is an emotional response of pregnant women related to the mother's concern for the well-being of herself and her fetus during pregnancy, childbirth, postpartum and when she has played a role as a mother. The purpose of this study was to determine the effect of mindfulness therapy training on reducing anxiety in mothers with first trimester pregnancies. This study used a descriptive case study method in mothers with first trimester pregnancies. In this study, purposive sampling was used with the following criteria: mothers with first pregnancies, experiencing anxiety, second trimester pregnancy and willingness to participate in this study. This study was conducted on November 14-16, 2024 at the Purbalingga Health Center by taking one pregnant woman. mothers with first pregnancies who received mindfulness therapy experienced a decrease in anxiety after 3 therapy sessions. Mindfulness therapy was accompanied by relaxation music. Patients who were given mindfulness therapy felt changes in their physical and psychological state. Patients were more relaxed and enjoyed their pregnancy and reduced the physical complaints they felt. Proven by the results of the DASS 42 questionnaire to 11. And after being given daily activity for mindfulness therapy, the results of the DASS 42 questionnaire became 6. This mindfulness therapy is effective in reducing anxiety in first trimester pregnant women accompanied by relaxation music. Mindfulness training can be used as an alternative psychological intervention to reduce anxiety in pregnant women. Mindfulness training has a significant positive effect on physical and psychological aspects.